Manipulation of magnetic nanostructures through low temperature metal-oxygen chemistry: Co/CoO exchange biased nanodonuts and Co nanotips - Phase, Deodatta; Choudhary, Ram Janay; Ganesan, V.; Reddy, V. Raghvendra; Gupta, Ajay; Selvi, N.; Kulkarni, Sneha; Ogale, Satishchandra (Solid State Communications, 2009)
Dense nanodonut and nanotip type morphologies are shown to self-evolve in Ultrathin cobalt films during growth under Vacuum, depending oil the level of oxygen incorporation and temperature. The nanodonut morphology forms at room temperature and the corresponding magnetic hysteresis shows exchange bias (similar to 35 Oe shift along the field axis), which is attributed to the presence of CoO and its exchange Coupling with cobalt. The morphology evolves into nanotip features with increase of growth temperature, with Concurrent elimination of the oxide component and exchange bias. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Co/CoO; Magnetic film; self assembly; Vacuum evaporation